A Low Cost, Flexible Atmospheric Pressure Plasma Jet Device With Good Antimicrobial Efficiency - Do Nascimento, Fellype [UNESP]; Da Graca Sampaio, Aline [UNESP]; Milhan, Noala Vicensoto Moreira [UNESP]; Gontijo, Aline Vidal Lacerda; Mattern, Philipp; Gerling, Torsten; Robert, Eric; Koga-Ito, Cristiane Yumi [UNESP]; Kostov, Konstantin Georgiev [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
Plasma sources suitable to generate low-temperature plasmas has been fundamental for the advances in plasma medicine. In this research field, plasma sources must comply with stringent conditions for clinical applications. The main requirement to be met is the patient and operator's safety and the ethical requirement of effectivity, which encompasses the electrical regulations, potential device toxicity, and effectiveness in relation to the desired treatment. All these issues are addressed by the German prestandard DIN SPEC 91315:2014-06 (DINSpec), which deals with the safety limits, risk assessment, and biological efficacy of plasma sources aimed for medical applications. In this work, a low cost, user-friendly, and flexible atmospheric pressure plasma jet (APPJ) device was characterized following the DINSpec guidelines. The device, which is still under development, proved to be safe for medical applications. It is capable of producing an APPJ with low patient leakage current and ultraviolet emission, gas temperature lower than 40 °C, production of harmful gases within the safety limits and low cytotoxicity. The most differentiating feature is that the device presented good antimicrobial efficacy even operating at frequency of the order of just a few hundred Hz, a value below that of most devices reported in the literature.
Keywords: DIN SPEC 91315; low-temperature plasma; plasma jet; plasma medicine